2015
DOI: 10.1371/journal.pone.0125686
|View full text |Cite
|
Sign up to set email alerts
|

Hyperpigmentation Results in Aberrant Immune Development in Silky Fowl (Gallus gallus domesticus Brisson)

Abstract: The Silky Fowl (SF) is known for its special phenotypes and atypical distribution of melanocytes among internal organs. Although the genes associated with melanocyte migration have been investigated substantially, there is little information on the postnatal distribution of melanocytes in inner organs and the effect of hyperpigmentation on the development of SF. Here, we analyzed melanocyte distribution in 26 tissues or organs on postnatal day 1 and weeks 2, 3, 4, 6, 10, and 23. Except for the liver, pancreas,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 45 publications
3
24
1
2
Order By: Relevance
“…A previous report has demonstrated that the three-week age is very important for the development of B-cells and provides an opportunity for some pathogenic infection18. We also found that the development of BF was significantly weaker in SF than in WL14. In the present study, numerous melanocytes were observed in the lamina propria and bursal nodes of BF in SF.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…A previous report has demonstrated that the three-week age is very important for the development of B-cells and provides an opportunity for some pathogenic infection18. We also found that the development of BF was significantly weaker in SF than in WL14. In the present study, numerous melanocytes were observed in the lamina propria and bursal nodes of BF in SF.…”
Section: Discussionsupporting
confidence: 68%
“…Thus, the reduced expression of the genes associated with the metabolic pathways in the BF of SF might contribute to a relatively weaker B-cell development and lower BF indices. In addition, in our previous work, we detected low levels of antibodies in SF after vaccination14. However, in the present study, the reduced expression of genes was related to the Toll-like and NOD-like receptor pathways, which might result from the proliferation, rather than the differentiation, of B-cells in the BF.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…After routine processing, the tissues were embedded in paraffin, cut into approximately 5-μm sections, and prepared for hematoxylin and eosin staining for histological examination [Han et al, 2015].…”
Section: Histopathology Of the Bursa Of Fabriciusmentioning
confidence: 99%
“…Unlike PIH, the association between melanoma and superficial innate immune responses is not well understood. Experiments using an interesting animal model, the silky fowl ( Gallus gallus domesticus Brisson), have suggested that hyperpigmentation may be related to inhibition of immune development and particularly to the degeneration of lymphoid organs [ 35 ]. The interaction between tyrosinase and MITF and its effect on melanogenesis has been well studied [ 17 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%